EFFECT OF PERIURETHRAL INJECTION ADIPOSE-DERIVED STEM CELLS IN NERVE HEALING AND VOIDING BEHAVIOR FOR THE TREATMENT OF STRESS URINARY INCONTINENCE IN A RAT MODEL - Rizaldi, Fikri; Purwati; Sandhika, Willy; Budiono; Hardjowijoto, Sunaryo (Indonesian Urological Association, 2021)
Objective: To investigate whether ADSCs are capable of nerve repair in stress urinary incontinence. Material & Methods: Thirty rats were allocated to five groups for receiving a periurethral injection with Phosphate Buffer Saline (PBS) (B1,B2) and Adipose-derived Stem Cells (C1, C2). Functional assessments with Voided Stain on Paper (VSOP) Method were reassessed at 2 and 4 weeks after injection. The rat SUI model was generated by Vaginal Distention (VD). The regeneration of peripheral nerve was evaluated by PGP 9.5 immunohistochemical staining. Results: Results revealed significant peripheral nerve differences between ADSC group and other groups in 28 days using PGP 9.5 staining. Our functional assessment, Voided Stain on Paper (VSOP), showed that ADSC group had significant improvement in 14 days; unfortunately, our 28 days improvement was not substantial. Conclusion: Periurethral injection of ADSCs improves urine pattern in SUI-induced rats and increase the amount of peripheral nerve. This method may be a potential strategy for SUI treatment.